Exhibitors’ perception of the 2017 Sanganai/Hlanganani World Tourism Expo. - Ngoni Courage Shereni; Nkululeko Mpofu; Khanyisani Ngwenya (African Journal of Hospitality, Tourism and Leisure, 2018)
The event management (meetings, incentives, conventions and exhibitions (MICE) industry has been booming of late (Lim and Zhu, 2018) and recording high growths rates over a number of years, as tourism players are prioritizing the product as a way to diversify their tourism offerings. The study consequently sought to explore exhibitors’ perceptions of the Sanganai/Hlanganani World Tourism Expo 2017. The study purposively sampled 60 respondents from a population of 340 exhibitors who attended the event at the Zimbabwe International Trade Fair (ZITF) grounds in Bulawayo, Zimbabwe. The study found that exhibitors perceived Sanganai/Hlanganani World Tourism Expo 2017 to be an important tourism event that brings considerable benefits to participants. The perception that exhibitors place on the event was determined by the quality of staff brought to the stand, the geographical dispersion of exhibitors from the venue, the amount of money spend on the exhibition, the number of times exhibitors have participated at previous editions as well as the diversity of sectors exhibiting at Sanganai/Hlanganani World Tourism Expo 2017. The study also unearthed challenges faced by exhibitors such a poor information dissemination, poor time management, booth management, slow internet connectivity and challenges in accessing the venue among others. The study concluded that the Sanganai/Hlanganani World Tourism Expo was perceived to be a highly beneficial event and well worth the attendance of exhibitors.